1983
DOI: 10.1002/j.1556-6978.1983.tb01736.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Effects of Modeling Through Role‐Play Practice

Abstract: The effects of yoking role-play practice to modeling treatments designed to teach the rudimentary counseling skill of reflection of feeling were investigated. Twenty-eight novice counselors-in-training were randomly assigned to one of the four treatment conditions: written model, videotape model, written model plus role-play practice, and videotape model plus role-play practice. Effectiveness was measured by ratings of students' oral responses to 16 videotaped client vignettes. The multivariate analyses reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…To minimize practice effects, I prepared eight different role-play scenarios, crossing four different presenting issues (cigarette smoking, obesity, marijuana use, and alcohol use) with two different actor demeanors (ambivalent and angry). Role-play length of 15 min was chosen on the basis of precedent in the training literature (e.g., K. Davis et al, 1985;Froehle et al, 1983;Hazler & Hipple, 1981). Each participant was assessed in two role plays before training and two role plays after.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize practice effects, I prepared eight different role-play scenarios, crossing four different presenting issues (cigarette smoking, obesity, marijuana use, and alcohol use) with two different actor demeanors (ambivalent and angry). Role-play length of 15 min was chosen on the basis of precedent in the training literature (e.g., K. Davis et al, 1985;Froehle et al, 1983;Hazler & Hipple, 1981). Each participant was assessed in two role plays before training and two role plays after.…”
mentioning
confidence: 99%
“…Research examining the effects of training on specific therapist techniques has demonstrated that a variety of behaviors, such as use of open-ended questions and reflective silence (Froehle, Robinson, & Kurpius, 1983; Robinson & Cabianca, 1985), reflection of affect (Froehle et al, 1983; Hazler & Hipple, 1981), and basic interviewing skills (Hosford & Johnson, 1983; Iwata, Wong, Riordan, Dorsey, & Lau, 1982), are amenable to training. In addition, more complex repertoires of verbal behavior have also been responsive to training.…”
mentioning
confidence: 99%
“…Yani bu süreçlerin dikkate alındığı psikolojik danışma oturumları daha başarılı sonuçlar vermektedir. Yapılan araştırmalar, deneyimsiz psikolojik danışmanların iletişimdeki tüm bileşenlere dikkat etmediklerini, yalnızca birkaç beceri ile sınırlı kaldıklarını, danışanların da terapi sürecinden daha az faydalandıklarını ortaya koymuştur (Errek & Randolph, 1982;Froehle, Robinson & Kurpius, 1983;Hazler & Hipple, 1981;O'Toole, 1979;Robinson & Cabianca, 1985). Grupla psikolojik danışma dersini alan psikolojik danışman adaylarının iletişimin tüm boyutlarında aldıkları puanların yükselmesi dersin önemli hedeflerinden birinin gerçekleştiği şeklinde yorumlanabilir.…”
Section: Tartişma Ve Sonuçunclassified
“…Westwood (1994) offered words of caution in describing group-based exercises. First, he pointed out that because of the importance of how exercises are Sampson (1996) Emmett & Harkins (1997; Golden (1999) Barak (1990); Kim & Lyons (2003) Emerson (1995) Colby & Long (1994) Dollinger (1989); Parker (1991); Pedersen (1994Pedersen ( , 1995; Schwitzer, Gonzalez, & Curl (2001); Westwood (1994) Getz & Protinsky (1994; Kane (1995); Kern & Riordan (1995) Goodman & Carpenter-White (1996) Baldo & Softas-Nall (1997) Froehle, Robinson, & Kurpius (1983); Rabinowitz (1997) presented, conducted, and debriefed, counselor educators should be appropriately trained in group-process and experience-based learning approaches. Second, he noted that student safety must be guaranteed by "a clear set of group norms or guidelines, which help structure the learning environment" (Westwood, 1994, para.…”
Section: Literature Reviewmentioning
confidence: 99%